How entrepreneurship, culture and universities influence the geographical distribution of UK talent and city growth. Issue 2 (6th March 2017) - Cowling, Marc; Lee, Neil
Abstract : Purpose: The creation and distribution of human capital, often termed talent, has been recognised in economic geography as an important factor in the locational decisions of firms (Florida, 2002), and at a more general level as a key driver of economic growth (Romer, 1990). The purpose of this paper is to consider how talent is created and distributed across the cities of the UK and the key factors which are driving this spatial distribution. They also consider what the economic outcomes of these disparities are for cities. Design/methodology/approach: The multivariate models can estimate the dynamic inter-relationships between human capital (talent), innovative capacity, and economic value added. These can be estimated, using talent as an example, in the form: human capital measure i = α 0 i + α 1 i innovative capacity + α 2 i quality of life + α 3 i labour market indicators + α 4 i economic indicators + α 5 i HEI indicators + β 6 i population demographics + β 7 i population + υ i . Findings: The first finding is that talent is unequally distributed across cities, with some having three times more highly educated workers than others. Talent concentration at the city level is associated with entrepreneurial activity, culture, the presence of a university, and to a lesser degree the housing market. This feeds into more knowledge-based industry, which is associated with higher gross value added. Research limitations/implications: The research is limited in a practical sense by the fact that UK data at this level have only become available quite recently. Thus, it is only possible to capture talent flows and city growth in a relatively small window. But the prospects going forward will allow more detailed analysis at the city level of the relationship between talent flows and local economic growth. And additional insights could be considered relating to the on-going changes in the UK university system. Practical implications: The question of whether universities are simply producers of talent or play a much broader and deeper role in the socio-economic landscape and outcomes of cities is an open one. This research has identified what the key drivers of city level economic growth and knowledge creation are, and sought to explain why some cities are capable of attracting and harnessing three times more talent than other cities. This has significant implications for the future development of UK cities and for those seeking to address these imbalances. Social implications: Universities are a major economic agent in their own right, but they are increasingly being asked to play a wider role in local economic development. The authors' evidence suggests that universities do play a wider role in the growth and development of cities, but that there are large discrepancies in the subsequent spatial distribution of the talent they create. And this has significant implications for those seeking to address these imbalances and promote a broader and less unequal economic landscape. Originality/value: The authors explore how cities create economic value via a process whereby talent is attracted and then this stimulates knowledge-based industry activity. The originality relates to several key aspects of the work. First, the authors look at the stock of talent, and then the authors explore how "new" talent from universities is attracted by looking at graduate flows around the cities of the UK, differentiating between top-level graduates and less talented graduates. The authors then allow a wide variety of economic, cultural, and population factors to influence the locational decision of talented people. The results highlight the complexity of this decision.